Pentingnya Edukasi Anti-Bullying pada Anak Sejak Dini di Panti Asuhan Ar-Rahman - Maysarah Maysarah; Bengkel Bengkel (ABDISOSHUM: Jurnal Pengabdian Masyarakat Bidang Sosial dan Humaniora, 2023)
Child growth is a phase where children search for their identity, in this phase children often do many things to explore themselves. The growth of children who want to explore themselves is not only supported from home but also from the environment around the child. In the growth phase children are more interested in spending a lot of time outside their home with their friends. The influence of friends makes a major contribution to bullying behavior, such as showing that bullying is not a problem but a normal thing. Bullying is a psychosocial problem by repeatedly insulting and demeaning other people with a negative impact on perpetrators and victims of bullying where perpetrators have more power than victims. This treatment has an impact on physical and emotional health and significantly affects the quality of life of a person. This also happens to the children at the Ar-Rahman orphanage, who sometimes like to isolate their friends, discriminate between friends, and fight among their own friends. In providing assistance through mini project practicum II activities, using the groupwork method through general or general intervention stages including: assessment, planning, intervention, monitoring, evaluation and termination. Where this process is a problem solving strategy given to clients, namely providing education about bullying which aims to reduce bullying to friends. And from this strategy it is hoped that clients can love friends and prevent bullying.